Genome-wide identification, classification and expression analysis of MYB gene family in coconut (Cocos nucifera L.) - Li, Jing; Guo, Shukuan; Min Htwe, Yin; Sun, Xiwei; Zhou, Lixia; Wang, Fangyuan; Zeng, Chunru; Chen, Shuangyan; Iqbal, Amjad; Yang, Yaodong (Frontiers in Plant Science, 2024)
MYB transcription factors regulate the growth, development, and secondary metabolism of plant species. To investigate the origin of color variations in coconut pericarp, we identified and analyzed the MYB gene family withinpresent in coconut was identified and subjected to analysis. Througha comprehensive genome-wide screening, we successfully identified a collection of 179 MYB genes in coconut as part of this study. Following Subsequent phylogenetic analysis, categorized these the 179 coconut MYB genes were categorized into 4-subfamilies:, namely 124 R2R3-MYB, 4 3R-MYB types, 4 4R-MYB type, and 47 unknown types. Additionally Furthermore, these genes were further divided into 34 subgroups,. Strikingly, with 28 out of these subgroups were successfully classified into the known subfamilies found in Arabidopsis thaliana. By mapping the CnMYB genes onto the 16 chromosomes of the coconut genome, we unveiled a collinearity association between them was unveiled. Moreover, a preservation of gene structure and motif distribution was observed across the CnMYB genes. In this Our research encompassed, we did a thorough investigation of the R2R3-MYB genes present in the Coconut coconut genome,. The current investigation encompassed including the chromosomal localization, gene assembly, conserved regions, phylogenetic associations, and promoter cis-acting elements of the studiedsaid genes. Additionally, we employed RNA-seq technology to spawn generate gene expression signatures of the R2R3-MYB genes amongst across distinctive coconut parts exhibiting diverse colors. To validate these profiles, we managed conducted